Characterization and Analysis of Ecological Tiles with Bacterial Cellulose and Industrial Waste - Yasmim F. Cavalcanti; Helen R. Da Fonseca; Alexandre D. Medeiros; Italo J. Durval; Andrea F. Costa; Claudio J.C. da Silva Junior; Leonie A. Sarubbo (Chemical Engineering Transactions, 2025)
The environmental issues arising from waste generation and extraction of natural resources, and cementitious materials in the construction sector are seeking to address these problems by substituting their main components with sustainable materials. Fibrocement, widely used in the production of roofing tiles, is composed of cement, and calcium silicate binders, and is reinforced with organic (vegetable cellulose), mineral, or synthetic fibers. However, the production of vegetable cellulose and its derivatives leads to increased wood consumption, causing environmental problems. Therefore, the aim of this project is to characterize and analyze sustainable tiles produced with bacterial cellulose (BC), combined with limestone filler (LF), textile industry waste (polyamide, PA), and sugarcane industry waste (sugarcane bagasse, SCB), comparing them with commercial tiles. The NBR 15310/2009 standard -Ceramic Components – Tiles was adopted as a comparative reference in the absorption tests and in the rupture and flexural load tests. The commercial tiles met the regulatory requirements, while the A6 samples (BC, LF, PA) showed an absorption index of 15%, within the stipulated limit. On the other hand, the A7 samples (BC, LF, SCB) exhibited an index of 20%, exceeding the maximum allowed value by 4%. In the rupture and flexural load tests, tile A6 surpassed the rupture load required by the standard by 5.4%, while tile A7 did not reach the minimum load of 1000 N required for simple bending. These results demonstrate the potential of sustainable and low-cost tiles for application in the construction industry, especially as building cladding.